Reconstruction of the pancreatic duct after pancreaticoduodenectomy: a modification of the Whipple procedure. - Katsaragakis, S; Antonakis, P; M Konstadoulakis, M; Androulakis, G. (J Surg Oncol, 2001)
BACKGROUND AND OBJECTIVES: Pancreaticoduodenectomy is still associated with high morbidity and mortality even though there has been significant progress in the field of pancreatic surgery and postoperative follow-up. The pancreatoenteric anastomosis, regardless of the technique used, is a major cause for both morbidity and mortality after Whipple procedure. To overcome all problems resulting from anastomotic leakage, we used external drainage of the pancreatic duct. METHODS: In 24 patients who underwent pancreaticoduodenectomy in our Department from 1986 to 1995, a modification to the standard Whipple procedure was performed. Instead of pancreaticoenteric anastomosis, external drainage of the pancreatic duct remnant was performed. The pancreatic duct was intubated with a silastic tube, the external end of which was sutured to the skin. All patients received substitution therapy with pancreatic enzymes. RESULTS: Mortality in our group of patients was 4%. No complications due to the external drainage of the pancreatic duct were reported, while no patient developed diabetes mellitus after surgery. CONCLUSIONS: External drainage of the pancreatic duct remnant can be used alternatively to pancreatoenteric anastomosis after pancreatoduodenectomy. The technique is safe and simple to perform and appears to reduce overall operative time. It may be an option for patients with significant comorbidity and/or intraoperative hemodynamic instability which mandates expeditious completion of the operation.
Keywords: Adenocarcinoma; Adult; Aged; Drainage; Female; Humans; Male; Middle Aged; Pancreatic Ducts; Pancreatic Neoplasms; Pancreaticoduodenectomy; Plastic Surgery Procedures; Retrospective Studies; Survival Rate